Performance of circular Oscillating Heat Pipe for highly adaptable heat transfer layout. (5th November 2021) - Okazaki, Shun; Fuke, Hideyuki; Ogawa, Hiroyuki
Highlights: Circular and serpentine OHPs were compared to study tube layout adaptability. The thermal resistance of a circular OHP was comparable with serpentine OHPs. Traveling pressure waves were observed in circular and serpentine OHPs. Decreasing the number of bends in a design does not affect thermal performance. OHPs with check valves can be routed with high adaptability. Abstract: We compared the thermal performance of two configuration types of Oscillating Heat Pipe (OHP) experimentally to investigate making heat transfer routing more adaptable. One type of OHP has the conventional configuration of closed-loop multiple-serpentine routing that uses U-shaped turns of 3.75 mm radius. The other type has the proposed circular ring configuration with a much larger radius of 1289 mm. Both types have the same pipe length so that the circular OHP can be considered an "unfolded" layout of the serpentine OHP. The circular OHP has alternating heated and cooled sections at locations corresponding to the sections of the serpentine model. Each type has ten sets of these sections with check valves; the OHPs were oriented horizontally. The working fluid was HFC-134a. Both types of samples functioned normally, and their thermal resistances were almost identical. Each OHP showed traveling pressure waves during operation, which indicated a phase difference at each measuring point. The experiment showed that OHPs, with check valves and alternating heated and cooled sections, can transfer heat without the need for a serpentine configuration and that heat transfer routing can be designed more adaptably.